Causes, experiences and consequences of the impact of chronic heart failure on the person´s social dimension: A scoping review - Olano‐Lizarraga, Maddi; Wallström, Sara; Martín‐Martín, Jesús; Wolf, Axel (Health & social care in the community, 2022)
Chronic heart failure (CHF) is a progressive and disabling condition that significantly impacts patients' daily lives. One of its effects is decreased opportunities to participate in social life, leading to reduced social interaction, loneliness, social isolation and lack of social support to continue with their daily life activities. This study aimed to explore the causes, experiences, and consequences of the impact of CHF on the social dimension of the person. According to the Arksey & O'Malley method, a scoping review of the literature was conducted to examine existing knowledge in the area, summarise existing evidence and identify gaps in the literature. The search was conducted in the PubMed, CINAHL, PsychINFO, Scopus, and Web of Science databases from January 2010 to November 2021. Twenty‐six articles were identified. The reasons why CHF influences the social dimension of the person were multifactorial and related to physical aspects, sociodemographics, lifestyle changes and the feelings experienced by these patients. Social relationships play a key role, and the benefits of good social relationships and the impact of poor or inadequate social support were identified. Furthermore, the influence of alterations in the social dimension on the CHF patient's clinical outcomes was described. This approach will help to detect and better understand the bidirectional influence that exists in each person between social isolation, relationships, and support life experiences, self‐care activities, and morbi‐mortality rates. These findings have shown the importance of detecting higher‐risk groups and systematically assessing factors related to the social dimension in all patients with CHF.